Formacja aszanckich specjalistów rytualnych - Wita, Grzegorz (Śląskie Studia Historyczno-Teologiczne, 2006)
The above article presents the means of discerning vocation and the ways to fulfill a function of ritual specialist in the Ashanti people from Ghana. It shows the procedure of interpretation of spirit possesion phenomenon and steps taken when a trance takes place. The author discussed also the following stages and ways of candidate initiation to become a ritual specialist: orders and taboos obliging the adepts, place and time of formation, persons playing a role of teachers, and also the okomyi rite, being a ritual of passage and incorporating into a state of Ashanti indigenous priesthood.